2008
DOI: 10.1007/s12245-008-0016-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary resuscitation: outcome and its predictors among hospitalized adult patients in Pakistan

Abstract: IntroductionOur aim was to study the outcomes and predictors of in-hospital cardiopulmonary resuscitation (CPR) among adult patients at a tertiary care centre in Pakistan.MethodsWe conducted a retrospective chart review of all adult patients (age ≥14 years), who underwent CPR following cardiac arrest, in a tertiary care hospital during a 5-year study period (June 1998 to June 2003). We excluded patients aged 14 years or less, those who were declared dead on arrival and patients with a “do not resuscitate” orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 20 publications
5
30
2
Order By: Relevance
“…1 There have been a number of studies after that, which have reported outcome and the predictors affecting outcome. [2][3][4][5] Cardiopulmonary resuscitation is a frequently performed medical intervention in healthcare facilities. Successful cardiopulmonary resuscitation after in-hospital cardiac arrest depends on basic and advanced life support systems, the ability to immediately defibrillate the arrested heart, and the quality of the CPR intervention (Beuret et al; Jorgenson 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 There have been a number of studies after that, which have reported outcome and the predictors affecting outcome. [2][3][4][5] Cardiopulmonary resuscitation is a frequently performed medical intervention in healthcare facilities. Successful cardiopulmonary resuscitation after in-hospital cardiac arrest depends on basic and advanced life support systems, the ability to immediately defibrillate the arrested heart, and the quality of the CPR intervention (Beuret et al; Jorgenson 1997).…”
Section: Introductionmentioning
confidence: 99%
“…But studies show a wide range of 'survival on discharge' (3-27%), which could be due to differences in the settings in which the CPR is performed and differences in inclusion/exclusion criteria. [5][6][7][8] To overcome this problem, the in-hospital Utstein style data collection (Utstein template) recommendation were published in 1997 and revised in 2004. 5,6 These recommendations defined a set of data elements that are essential for documenting in-hospital cardiac arrests and suggested guidelines for reviewing, reporting, and conducting research on this topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of CPR, and initial cardiac activity did not significantly influence 30-day-mortality in our study, but earlier findings reported elevated mortality rate after nonshockable rhythms (20) and the duration of CPR as an independent predictor of mortality. (21,22) It is well known that the original ILCOR guideline recommended TH after ventricular fibrillation but for other rhythms the "may also be beneficial" statement was used. (6) In the present study, serum lactate levels in the TH group were significantly higher than in the NT group on ICU admission and in the 12 th and 36 th hours after ROSC.…”
Section: Protein S100b Levelsmentioning
confidence: 99%
“…[1][2][3][4] Guidelines therefore exist for terminating resuscitative efforts in cases of cardiac arrest that are deemed futile. 5,6 Nonetheless, successful resuscitation and good recovery after prolonged arrest have been documented.…”
mentioning
confidence: 99%